Sustainable Opportunities of Educational Facilities Provided to the Imprisoned Women’s Children in Karachi’s Central Jail - Faizi, Waqar Un Nisa; Dr. Anila Fatima Shakeel; Dr. Rabia Abdul Karim (European Journal of Multidisciplinary Studies, 2017)
This study will discuss the sustainable opportunities regarding educational facilities provided to the children of imprisoned women in the different jails of Pakistan particularly in Central Jail of Karachi. It will also discuss the importance of educational facilities which are required for the mental and personal growth of the children as education has the capability to enhance the general knowledge and the personality of any individual. Education is extremely important for the children whether they live in a society or in prison, because they are the future of any country. So, the point of discussion in this paper will be the provision of educational facilities and sustainable opportunities regarding these facilities to the children of imprisoned women in Karachi and other countries of the world.
Keywords: Imprisoned, educational facilities, criminal activities, positive atmosphere